The study of the baking ovens by computer simulation - Litovchenko, Igor (My University, 2013)
Configuring ovens for baking bread is a complex scientific and industrial problems. Find the best modes of operation allows computer simulation of aerodynamic and thermal processes in the heating ducts and the baking chamber.
Keywords: furnace; heat; temperature; baking; печи; теплота; температура; выпечка; печі; температура; випікання; кафедра машин і апаратів харчових та фармацевтичних виробництв